2014
DOI: 10.1002/jsfa.6703
|View full text |Cite
|
Sign up to set email alerts
|

Nutritive value of maize silage in relation to dairy cow performance and milk quality

Abstract: Maize silage has become the major forage component in the ration of dairy cows over the last few decades. This review provides information on the mean content and variability in chemical composition, fatty acid (FA) profile and ensiling quality of maize silages, and discusses the major factors which cause these variations. In addition, the effect of the broad range in chemical composition of maize silages on the total tract digestibility of dietary nutrients, milk production and milk composition of dairy cows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
178
1
11

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 194 publications
(253 citation statements)
references
References 100 publications
(246 reference statements)
21
178
1
11
Order By: Relevance
“…The lowest contents of NDF, ADF and ADL were determined in the maize hybrid ZP 434 that is a dent with a hard endosperm. Obtained results are in accordance with results more recently published by foreign authors who had recorded higher contents of NDF, ADF and ADL in morphological parts, but also in the whole plant of dent maize in relation to hard forms of dent maize (Ferreira et al, 2013 andKhan et al, 2015).…”
Section: Chemical Composition and Content Of Lignocellulosic Fibres Isupporting
confidence: 92%
“…The lowest contents of NDF, ADF and ADL were determined in the maize hybrid ZP 434 that is a dent with a hard endosperm. Obtained results are in accordance with results more recently published by foreign authors who had recorded higher contents of NDF, ADF and ADL in morphological parts, but also in the whole plant of dent maize in relation to hard forms of dent maize (Ferreira et al, 2013 andKhan et al, 2015).…”
Section: Chemical Composition and Content Of Lignocellulosic Fibres Isupporting
confidence: 92%
“…In their two year study at northern latitudes (56 o N-59 o N) the DM content of three forage maize hybrids varied between 160-370 g kg -1 at approximately 150 DAS. Khan et al (2015) concluded that the DM intake, milk yield and milk protein content increased with advancing maturity, reaching an optimum level for maize ensiled at DM contents of 300-350 g kg , and then declined slightly at further maturity beyond 350 g kg -1…”
Section: Discussionmentioning
confidence: 99%
“…This agrees with the in vitro results of Lynch et al (2012) between 126 DAS and 153 DAS while the further delay of harvest to 174 DAS decreased digestibility. Many investigations have revealed the negative effects of increasing maize maturity on digestibility, mainly when maize is harvested with high DM content (≤ 350 g DM kg -1 ; Khan et al 2015). This indicates changes in the cob/stover ratio and changes in the digestibility of the nutrient components while the profile of digestibility changes differ among hybrids (Lynch et al 2012, Khan et al 2015.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations